Do Galactolipid Synthases Play a Key Role in the Biogenesis of Chloroplast Membranes of Higher Plants? - Joana Rocha (Frontiers in Plant Science, 2018)
A unique feature of chloroplasts is their high content of the galactolipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), which constitute up to 80% of their lipids. These galactolipids are synthesized in the chloroplast envelope membrane through the concerted action of galactosyltransferases, the so-called ‘MGDG synthases (MGDs)’ and ‘DGDG synthases (DGDs),’ which use uridine diphosphate (UDP)-galactose as donor. In Arabidopsis leaves, under standard conditions, the enzymes MGD1 and DGD1 provide the bulk of galactolipids, necessary for the massive expansion of thylakoid membranes. Under phosphate limited conditions, plants activate another pathway involving MGD2/MGD3 and DGD2 to provide additional DGDG that is exported to extraplastidial membranes where they partly replace phospholipids, a phosphate-saving mechanism in plants. A third enzyme system, which relies on the UDP-Gal-independent GGGT (also called SFR2 for SENSITIVE TO FREEZING 2), can be activated in response to a freezing stress. The biosynthesis of galactolipids by these multiple enzyme sets must be tightly regulated to meet the cellular demand in response to changing environmental conditions. The cooperation between MGD and DGD enzymes with a possible substrate channeling from diacylglycerol to MGDG and DGDG is supported by biochemical and biophysical studies and mutant analyses reviewed herein. The fine-tuning of MGDG to DGDG ratio, which allows the reversible transition from the hexagonal II to lamellar α phase of the lipid bilayer, could be a key factor in thylakoid biogenesis.